10,000 deaths that go annoticed every year - Abd Razak, Dzulkifli (2008)
LAST week, Malaysia lost another entrepreneur closely associated with the automotive industry. Like the late Tan Sri Yahya Ahmad of Proton, the demise of Tan Sri S.M. Nasimuddin S.M. Amin will leave a lasting mark on Malaysia's emerging car industry. Nasimuddin died of lung cancer at the young age of 53 in Los Angeles where he had been undergoing treatment after discovering that he was suffering from an advanced stage of lung cancer. What is sad is how victims of this preventable scourge go down real fast once they pass a certain stage even without knowing it. To lose an astute entrepreneur, who had created a multimillion empire, in this way is very sad.